PENGARUH BAURAN PEMASARAN DAN CITRA DESTINASI TERHADAP MINAT BERKUNJUNG KEMBALI DI DESA WISATA SELO PARK NGANJUK - Susanto, Budi; Nursamsu, Nursamsu (Jurnal Riset Entrepreneurship, 2020)
The purpose of this study was to determine the effect of Marketing Mix and Destination Imagery on the Interest of Returning Tourists in Selo Park Jatikalen Nganjuk. The study sample was taken as many as 100 respondents from visitors to Selo Park Jatikalen Nganjuk. The analytical tools used in this study are instrument analysis, validity test, reliability test, classic assumption test, multiple linear analysis and hypothesis testing. The results showed that the influence of the Marketing Mix had a significantly positive effect on the interest of returning tourists to Selo Park. The results showed that the influence of Citra Destination had a significant positive effect on the interest of returning tourists to Selo Park. Both of these variables also affect together the Interest of Revisiting Selo Park attractions.Based on the results of this study, the manager of Selo Park tourism object can increase the Interest of Tourist Return Visit by increasing the Marketing Mix and Destination Image variable, because the increasing of these two variables is increasing the Interest of Selo Park Tourist Returning Visit.